Personal Branding of Da'wah Ustadz Luqmanul Hakim on Instagram @luqmanulhakimpontianak Account - Zulfan Dzulfikar; Veri Setiawan (Universitas Darussalam Gontor, 2024)
Personal branding is a process by which humans are seen and valued as a brand Personal branding is the process by which individuals are perceived and evaluated as a brand by their target market. It is also the art of attracting more clients by actively shaping public perception. One way to build public perception is through da’wah. In establishing personal branding for da’wah, one effective method is utilizing social media, particularly Instagram. The purpose of this research is to understand the personal branding of Ustadz Luqmanul Hakim. The author used a descriptive qualitative research method, where data was collected in the form of images or words. This research applies the theory proposed by Peter Montoya, which states that personal branding is considered successful if it fulfills eight concepts: Specialization, Leadership, Personality, Distinctiveness, Visibility, Unity, Persistence, and Good Reputation. The results of this study indicate that all eight concepts of personal branding described in Peter Montoya's theory are present and observable in each of Ustadz Luqmanul Hakim's Instagram posts. The application of personal branding concepts on Instagram has allowed Ustadz Luqmanul Hakim to specialize in his da’wah theme, which is charity. In terms of leadership, he successfully encourages the public to honor orphans. His personality is good, dignified, and humble. His distinctiveness lies in his language and attire. He promotes his preaching consistently on Instagram to ensure visibility. Unity is reflected in how he practices what he preaches in his daily life. He demonstrates persistence by continuing his preaching efforts even in remote areas. By doing all of this, Ustadz Luqmanul Hakim has earned a good reputation in the eyes of the public. Keywords: Personal branding, Ustadz Luqmanul Hakim, Da'wah and Instagram.